Training Effect of Straight-Line Trajectory with the Ball on Dribbling Results on Disporasu Medan Football Players Aged 14-17 Years Old - Melki Sedek Lumbantobing; Albadi Sinulingga (Journal of Indonesian Active in Sports, 2024)
The objective of this study was to examine the impact of straight-line trajectory ball training on the dribbling abilities of players at the Disporasu Football School, aged between 14 and 17 years old, in Medan City, Indonesia. The research addressed the observed deficiencies in dribbling abilities, including players' difficulty in maintaining close ball control and the monotony of existing training methods. The study employed an experimental one-group pre-test post-test design and involved 17 athletes, representing the entire population of the age group at the school. The intervention comprised seven variations of straight-line trajectory ball training, conducted thrice weekly for a period of six weeks between September 21st and December 12th, 2022. The dribbling ability of the subjects was evaluated using a standardized dribbling test before and after the training period. The data were analyzed using paired sample t-tests, with normality and homogeneity checks performed prior to hypothesis testing. The results demonstrated a notable enhancement in dribbling proficiency following the intervention, with the mean dribbling time reducing from 21.18 to 19.66 seconds. The study's findings indicate that straight-line trajectory ball training significantly enhances dribbling ability in youth soccer players. These results provide coaches and trainers with an evidence-based approach to improve essential soccer skills during a crucial developmental period. The research contributes to a broader understanding of skill acquisition in soccer, offering practical insights for optimizing player performance and engagement. Additionally, the study underscores the significance of structured, progressive training programs in youth soccer development and provides a valuable template for ongoing assessment and refinement of training methods.